Estudio de la resistencia de los microorganismos a la ciprofloxacina en pacientes con infecciones de vías urinarias de 30 a 60 años que se atienden en el subcentro de salud del Barrio Teniente Hugo Ortiz del cantón Santa Rosa durante los meses de diciembre del 2013 a enero del 2014. - Ramos Sarmiento, Byron Rodrigo (2015)
Among the various factors that have contributed to the significant increase in life expectancy over the past century is undoubtedly the control of many infectious diseases through interventions such as vaccines and antibiotics specifically. Bacterial resistance is a growing phenomenon with enormous social and economic implications given the increased morbidity and mortality, increased costs of treatment and long hospital stays generated.